1999
DOI: 10.1021/ja9925249
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Gypsetin, Deoxybrevianamide E, Brevianamide E, and Tryprostatin B:  Novel Constructions of 2,3-Disubstituted Indoles

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
106
0
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 49 publications
7
106
0
5
Order By: Relevance
“…Preechinulin (5) [17][18][19][20][21] was synthesized starting from isoprenyl L-tryptophan derivative 15a (Chart 4). Deprotection of N-phthaloyl group in 15a [22][23][24] with hydrazine and coupling of the resulting amine with N-Boc-L-Ala gave 16a. Deprotection of N-Boc group in 16a and thermal cyclization afforded preechinulin (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preechinulin (5) [17][18][19][20][21] was synthesized starting from isoprenyl L-tryptophan derivative 15a (Chart 4). Deprotection of N-phthaloyl group in 15a [22][23][24] with hydrazine and coupling of the resulting amine with N-Boc-L-Ala gave 16a. Deprotection of N-Boc group in 16a and thermal cyclization afforded preechinulin (5).…”
Section: Resultsmentioning
confidence: 99%
“…The organic layer was evaporated to give a crude residue, which was purified by a preparative TLC (hexanes : EtOAcϭ2 : 1) to afford 3 (46 mg, 52%) as a yellow amorphous solid. (1,1-dimethyl-2-propenyl)-1H-indol-3yl]propionate 16a To a solution of 15a 22,23) (350 mg, 0.84 mmol) in EtOH (8.5 ml) was added hydrazine monohydrate (0.14 ml, 2.94 mmol), and the mixture was stirred at rt for 3 d. The mixture was filtrated and washed with MeOH, and the resultant filtrate was evaporated to give a crude amine.…”
Section: Ethyl 2-(tert-butyloxycarbonylamino)-3-[(z)-2-(11-dimethyl-mentioning
confidence: 99%
See 1 more Smart Citation
“…Signals for the four protons at positions 4, 5, 6 and 7 of the indole ring were clearly observed (Table S1), and revealed that the prenyl moiety is connected to N-1 or C-2 of the indole ring. The signals of the methyl groups in the reverse prenyl moieties attached to C-2 of the indole rings of some diketopiperazine derivatives, for example, in echnulin-and isoechinulin-type alkaloids, [2][3][4] in deoxybrevianamide E [5] or okaramines, [6,7] were usually found in the range of 1.40 to 1.55 ppm. In comparison, the signals of the methyl groups in the prenyl moieties of the enzymatic products of CdpNPT are significantly up-field shifted to 0.9 to 1.1 ppm.…”
mentioning
confidence: 99%
“…Link and Overman (43) have also reported a bis-enolate alkylation approach to bispyrroloindoline containing natural products. The Danishefsky group has used enantiopure tryptophan-based starting materials for their asymmetric synthesis of amauromine and the ardeemins (44,45). Their strategy relies on stereochemical induction from a resident stereocenter derived from tryptophan in a cascade selenationring-closing protocol.…”
mentioning
confidence: 99%